A Criticality and depletion analysis of the European Lead-Cooled Training Reactor (ELECTRA) - Ana Luiza Pereira Oliveira; Clarysson Alberto Mello da Silva (Brazilian Journal of Radiation Sciences, 2022)
In this article, a criticality and depletion analysis of the European Lead-Cooled Training Reactor (ELECTRA), a low-power, compact, fast lead-cooled reactor, was performed. The active core model and simulations were made by using the MCNPX code. First, the model is compared with the reference and the influence of the reflector radius on the system is analyzed. Secondly, it was simulated the fuel combustion after 30 years of continuous operation of the ELECTRA, managing to evaluate the transmutation of a reprocessed fuel in a compact lead-cooled reactor.